A New Score for Predicting Acute Gastrointestinal Bleeding in Patients Administered Oral Antiplatelet Drugs - Lv, Meina; Zheng, Xiaochun; Wu, Tingting; Chen, Wenjun; Jiang, Shaojun; Zhang, Hongqin; Xu, Fangda; Zhang, Jinhua (Frontiers in Pharmacology, 2021)
Antiplatelet drugs may increase the risk of gastrointestinal bleeding. Currently, there is no specific score for predicting the risk of gastrointestinal bleeding caused by oral antiplatelet drugs. In this study, the gastrointestinal bleeding risk score was established and compared with the CRUSADE score in order to reduce the occurrence of clinical gastrointestinal bleeding events. Our study included 4052 patients who received oral antiplatelet drugs. Data was obtained from the patient medical records inpatient system. Cases of acute gastrointestinal bleeding and mortality were recorded. The bleeding score was established by logistic regression, area under the receiver operating characteristic curve, and the Hosmer–Lemeshow test. During the six-month follow up, 171 patients had acute gastrointestinal bleeding. The mortality rates of patients in the bleeding and non-bleeding groups were 24.6% and 4.7%, respectively. A multivariate analysis revealed that an age of >65 years, anemia, recent major bleeding, a history of gastrointestinal bleeding, combined oral anticoagulants, dual antiplatelet therapy are risk factors, and combined proton pump inhibitors are protective factors for acute gastrointestinal bleeding. We used these risk factors to establish a score for predicting acute gastrointestinal bleeding, named (ABC)2D score. The area under the curve for (ABC)2D score was 0.857 (P < 0.001); higher than the CRUSADE score of 0.693 (P < 0.001). The Hosmer–Lemeshow P value was 0.324. We developed the (ABC)2D score based on seven risk factors (i.e., age, anemia, recent major bleeding, a history of gastrointestinal bleeding, no-proton pump inhibitors use, combined oral anticoagulants, dual antiplatelet therapy). (ABC)2D score was superior to the CRUSADE score. This new risk-scoring model may help to identify patients at a significant risk of gastrointestinal bleeding.